Designing social identities : a case study of a primary school theatrical performance by Zulu children in an English ex-model C school - Alborough, Clare Louise (Centre for Applied Language and Literacy Studies and Services in Africa, 2014)
This multimodal case study investigates the discourses that emerge in a theatrical performance, constructed and performed by a group of grade seven, Zulu speaking students as a representation of themselves. The performance was set in an ex-model C primary school in Kwa-Zulu Natal and reflects the tensions between the students' identities that are located in the different fields of home, school, traditional settings and urban settings. The study is qualitative in nature, with the performance text being a participatory, creative, multi modal, joint-construction involving the participants and the researcher. The performance was structured so that each scene represents one of the participants' social fields. The analysis of the performance follows this structure and explores the way discourses and identities emerge from the Traditional, Home, School and Urban scenes of the performance. The study draws on the New London Group's Multiliteracies theory, using the concepts of discourse, identity, interest and design, as well as drawing on Bourdieu's notions of field and capital. The study makes use of social semiotic analysis, drawing particularly from Kress and van Leeuwen's visual grammar, to explore the multi modal nature of the performance, analysing the linguistic mode alongside those of the visual, the gestural and the spatial. The study attempts to be consistent with the multimodal nature of the performance and so presents the data through photographs, sketches and video clips integrated with the written text. The study alms to amplify the participants' voice through the richness of their representation. It attempts to contest the notion that marginalised people are powerless in the face of hegemonic discourses, asserting rather that there is always agency.